Capturing Moments to Analyze Students’ Transformative Thinking through Photovoice in an English Language Teaching Classroom: Students’ Transformative Thinking in ELT - Afifah, Wiwiek (Universitas Ahmad Dahlan, 2023)
This study aims to explore how students’ thinking evolved during joining the ELT class, how their insights changed, what moments lead students to undergo the transformation, and what ELT students believed about the TT contribution to ELT. Photovoice, a participatory research method was employed to these determined research purposes. Approximately 75 students, aged 19-20 years old were invited to participate in this study. They were instructed to submit two pictures. Each picture was given 5 questions: what you saw here, what really happened, how did this relate to your life, why did this occur, and what could you do regarding EL II. A questionnaire was designed to be filled out by the students using Google Forms, which was used as the second data to complete the pictures’ interpretation. Data analysis then used the model from Erlingsson and Brysiewicz (2017) consisting of four steps: condensation, coding using MAXQDA, categorization, and finalizing the themes. This study provided insightful information about the dynamics of transformative thinking in ELT classrooms through photovoice. The results helped us understand the cognitive and affective aspects of English language learning, which guided the pedagogical strategies used in ELT classes to promote students’ transformational thinking.